Ancient diversity and geographical sub-structuring in African buffalo Theileria parva populations revealed through metagenetic analysis of antigen-encoding loci - Hemmink, Johanneke D.; Sitt, Tatjana; Pelle, Roger; Klerk-Lorist, L.M. de; Shiels, B.; Toye, Philip G.; Morrison, W.I.; Weir, W. (Elsevier, 2018)
An infection and treatment protocol involving infection with a mixture of three parasite isolates and simultaneous treatment with oxytetracycline is currently used to vaccinate cattle against Theileria parva. While vaccination results in high levels of protection in some regions, little or no protection is observed in areas where animals are challenged predominantly by parasites of buffalo origin. A previous study involving sequencing of two antigen-encoding genes from a series of parasite isolates indicated that this is associated with greater antigenic diversity in buffalo-derived T. parva. The current study set out to extend these analyses by applying high-throughput sequencing to ex vivo samples from naturally infected buffalo to determine the extent of diversity in a set of antigen-encoding genes. Samples from two populations of buffalo, one in Kenya and the other in South Africa, were examined to investigate the effect of geographical distance on the nature of sequence diversity. The results revealed a number of significant findings. First, there was a variable degree of nucleotide sequence diversity in all gene segments examined, with the percentage of polymorphic nucleotides ranging from 10% to 69%. Second, large numbers of allelic variants of each gene were found in individual animals, indicating multiple infection events. Third, despite the observed diversity in nucleotide sequences, several of the gene products had highly conserved amino acid sequences, and thus represent potential candidates for vaccine development. Fourth, although compelling evidence for population differentiation between the Kenyan and South African T. parva parasites was identified, analysis of molecular variance for each gene revealed that the majority of the underlying nucleotide sequence polymorphism was common to both areas, indicating that much of this aspect of genetic variation in the parasite population arose prior to geographic separation.